À QUERIDA LEITORA: BREVE ANÁLISE DAS CARTAS FICCIONAIS EMITIDAS A G.M. EM DOIS ROMANCES ALENCARIANOS (Miscelânea: Journal of Literature and Social Life, 2025)
Our proposal is to investigate the construction of the epistolary novels Diva (1864) and Lucíola (1862), written by José de Alencar, focusing on the character identified as P. or Paulo. First, we will present the funcions of both the serialized novel and epistolary novel. After that, we will demonstrate how Paulo can be understood as an alter ego of José de Alencar himself, through examples of letters in the novels.